OPTIMALISASI PEMANFAATAN KOTORAN TERNAK MENJADI PUPUK ORGANIK DENGAN DEKOMPOSER AGROZYME DI DESA SENGKOL - Aisy, Nisrina Maharatul; Putra, I Wayan Bratha Permana; Jurnal Wicara; Putri, Chairatun Hisyani; Khalid, Juniar; Lestari, Widya; Putri, Bunga Shirtuvillaily Yuniar; Ardaelifa, Elya Trainy; Zahara, Lauza Agisni; Moztaqi, Lalu Muhammad Khalif (Jurnal Wicara, 2025)
Improper management of livestock manure may cause negative impacts to the environment and human health. This condition would get worse when animal pens are located close to residential areas. On the other side, livestock manure actually could be utilized as organic fertilizer due to its nutrient content such as Nitrogen (N), Phosphorus (P), and Potassium (K). Therefore, socialization and training on the utilization of livestock manure into organic fertilizer is necessary as an environmentally friendly solution while creating synergy between the livestock and agricultural sectors. This community service activity carried out in Dusun Loang Landak, Sengkol Village, Pujut District, Central Lombok Regency, West Nusa Tenggara, with implementation methods including (1) Observation, (2) Planning, (3) Implementation, and (4) Evaluation. The socialization and training were attended by 30 participants consisted of farmers, livestock breeders, and students in Dusun Loang Landak. The materials delivered included the urgency of livestock waste management, the benefits of Agrozyme decomposer, and the process of making organic fertilizer. Participants showed high enthusiasm by actively engaging in discussions about application of organic fertilizer in agricultural fields. During the training session, the participants directly practiced making organic fertilizer so that they could practice it independently. This activity successfully improved the knowledge and skills of Sengkol Village community members in processing cattle manure into organic fertilizer.